KOLEKSI TUMBUHAN TERANCAM KEPUNAHAN DI KEBUN RAYA BOGOR - Kusuma, Yayan Wahyu Candra; Dodo, Dodo; Widyatmoko, Didik (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2008)
Indonesia possesses 386 plant species that are categorized as threatened. Dipterocarpaceae contributes the largest number, reaching 36.79 % of the total threatened plant species, followed by Myristicaceae (13.73 %) and Nepenthaceae (6.99%). Of these 386 threatened species, 29.27 % are critically endangered, 17.88% are endangered, and 52.85 % are vulnerable. Bogor Botanic Garden recently maintains 68 threathened plant species if Orchidaceae and Nepenthaceae members are not included on the list. Two species have been regarded as extinct, namely Dipterocarpus cinereus and Calamus spectabilis, while two other species are regarded as extinct in the wild (Mangifera casturi, and Mangifera rubropetala). This information can be useful for everyone for different purposes, especially for those who concern in the conservation of threatened plant species in Indonesia.